EFEITO DA LASERTERAPIA DE BAIXA INTENSIDADE NA MODULAÇÃO GÊNICA DE FATORES RELACIONADOS A CICATRIZAÇÃO DE ÚLCERAS DE PACIENTES DIABÉTICOS - Ruh, Anelice Calixto (2013)
Pressure sores (PS) are wounds found mainly on bone surfaces where the tissue under pressure suffers ischemia which leads to cellular lesion. The causes of such lesion are several and its healing process depends on several factors, intrinsic and extrinsic to the individual. The objective of this study was to analyze the tissue expression of growth factors, IL6, TNF, VEGF, TGF, which take part in the tissue healing process under the effect of low-level laser InGaAIP. The study was approved by the Ethics Committee at UEPG and the individuals informed and made aware of the aims of the study. The group under study comprised 8 volunteers aged 30 to 75 years old, admitted at the Santa Casa de Misericórdia de Ponta Grossa (SCMPG) hospital, who presented sacroiliac PS, ranked as degree II, III or IV according to NPUAP (2009), both sexes. The PSs were photographed for classification and gross analysis of the lesion area through the program Image Pro Plus 6.0®. Samples of periulcerated tissue were obtained through biopsy before and after laser therapy. The biopsies were destined to the qRT-PCR (Quantitative Real Time PCR). Results revealed that in the gross evaluation of the wound there was improvement of the appearance and size of the lesion area, with increase in the granulation tissue. For the qRT-PCR tests, results point out a non-significant expression of differential growth factors between pre and post laser therapy condition. Based on these results it was possible to conclude that the laser therapy helps the healing process, but the expression of growth factors suffers influence of aspects that interfere in the healing process such as age, underlying pathology, medication, patient’s general condition, nutrition, and skin condition.